Propuesta para la reducción de pérdidas no técnicas en el área de servicio de la Empresa Pública Estratégica Corporación Nacional de Electricidad CNEL EP, Unidad de Negocio Los Ríos - Alulema Asqui, Verónica Paulina (2018)
Resumen: The objective of this graduation thesis is to design a proposal for reducing non-technical energy losses in the geographic service area of the CNEL EP Los Ríos Business Unit. This proposal is based on campaigns aimed at strengthening active client participation, proving knowledge to the user about the damages of energy theft, conveying the benefits of the legal consumption of electricity, describing the parameters of the electric power service, and providing tips for saving energy. The best way to reduce non-technical energy losses is to raise awareness among the public about the risk of illegal connections or tampering with meters. Real savings are possible through the adoption of good energy efficiency practices in the home.